(untitled) (Agroindustrial Science, 2022)
The Brevicoryne brassicae aphid is an important pest of several plants of the Brassicaceae family worldwide. In the Mantaro Valley-Peru, it causes economic losses in cabbage and broccoli crops. Myzus persicae is the most important pest in potato cultivation. Myzaphis rosarum colonizes both wild and cultivated rose bushes and trees. To control it, farmers use toxic chemical insecticides that cause health problems. Faced with this problem, biocontrol is an important component of sustainable production to control pests. Hippodamia convergens is a predator of aphids, so it is necessary to know its biology and predation in its different prey. The objective was to determine the duration of the development stages, longevity, fecundity and performance of the predator H. convergens reared with cabbage aphids B. barssicae, Myzaphis rosarum and Myzus persicae. The completely randomized design was used, with 10 repetitions and three treatments or species of aphids. The aphid species used as food for the predator influenced the duration of preimaginal and adult development. Egg-adult development was longer with 34.1 days with B. brassicae and shorter with M. rosarum and M. persicae with 22.8 and 22.5 days respectively. Cabbage glucosinolates absorbed by B. barssicae negatively affected the growth rate, development, weight gain, survival, fecundity and predation capacity of H. convergens.